A conceptual beachhead: "Beaches and dunes of human-altered coasts" by Karl F. Nordstrom (1994). (June 2022) - Lazarus, Eli D
Approaching 30 years since its publication in Progress in Physical Geography, Nordstrom's work from 1994 reads like an uncannily current synopsis of grand challenges in interdisciplinary coastal science. The article is a playbook of testable hypotheses for emerging and future empirical coastal research.